Antibiotics resistance of Vibrio spp. isolated from aquaculture water in some areas of Northern Vietnam - Ngô, Thị Huyền; Vũ, Xuân Nghị; Lê, Đặng Lâm Oanh; Đặng, Lệ Quỳnh; Lê, Thị Tuyết Mai; Phạm, Thị Tâm; Đồng, Văn Quyền; Vũ, Thị Bích Huyền (Hue University Journal of Science: Natural Science, 2022)
Antibiotic resistance is a serious global problem, especially in aquaculture. In this study, we evaluated the antibiotic resistance of Vibrio spp. isolated from aquaculture water in shrimp and fish farming areas of five provinces of Northern Vietnam. There were 86 bacterial samples isolated, belonging to four species of Vibrio sp., in which V. parahaemolyticus and V. alginolyticus were the two most widespread species on selective TCBS và ChroMagarTMVibrio media. These bacterial samples were used to evaluate their resistance to 13 antibiotics with the agar plate diffusion method according to CLSI standards. The results show that these samples have a very high rate of resistance to ampicillin (100%), amoxicillin (98.84%), streptomycin (84.88%), and oxytetracycline (69.77%); the lowest resistance rate is to phenicol antibiotics: chloramphenicol (32.56%) and florfenicol (31.4%). The multiple antibiotic resistance (MAR) indices were recorded from 0.15 to 1.0. Two isolates were resistant to all 13 antibiotics. The bacterial isolates from aquaculture water of the five areas have a high resistant rate (100%) from four to eight antibiotics. This result suggests a relationship between antibiotic resistance of the bacterial strains and the current use of antibiotics in aquaculture, and this is one of the important bases for developing strategies and plans on the use and control of antibiotics in aquaculture in the localities.